Effect of Bottom Profiles on Pneumatic Performance of an Oscillating Water Column in Regular Waves: A Numerical Modelling Approach - Lim , Jia Rou (IRC, 2019)
Malaysia is blessed with a total of 878 islands featuring stunning beaches, tropical forests and diverse cultures. For some remote islands, the most conventional method of generating energy is through the use of diesel generators. This option may not be sustaining in a long run. Since these islands are surrounded by a large extent of shorelines, marine energy becomes a promising source of renewable energy